Relasi Islam dan Budaya Lokal: Kajian Komunikasi Antar Budaya pada Tradisi Ziarah Makam Wali Nyatok di Desa Rembitan Pujut Lombok Tengah - Yuyun Ekawati (Bulletin of Pedagogical Research, 2025)
Nyatok in Rembitan Village which is very different from the tomb pilgrimage in general. This type of research uses a qualitative descriptive research method to describe and analyze a situation in the object of research. The data collection methods used are observation, interviews, and documentation. The focus of this research discusses several things including: (1) How is the relationship between Islam and local culture in the practice of pilgrimage to the tomb of Wali Nyatok in Rembitan Village, (2) The process of communication between local culture and Islam in the practice of pilgrimage to the tomb of Wali Nyatok, (3) knowing how the forms of acculturation of religious values ​​and local cultural values ​​​​in the practice of pilgrimage to the tomb of Wali Nyatok. The results of the research that has been carried out show that: (1) In the practice of pilgrimage to the tomb of Wali Nyatok, there is a relationship between Islam and local culture so that it produces cultural acculturation that can be seen from the series of pilgrimage processions to the tomb of Wali Nyatok,2) The process of cultural acculturation in the practice of pilgrimage to the tomb of Wali Nyatok is also inseparable from intercultural communication, namely Islamic culture and the local culture of the people of Rembitan Village, (3) In the practice of pilgrimage to the tomb of Wali Nyatok carried out by the Rembitan people, there are forms of acculturation in religious and cultural values, each of which has its own meaning which is often interpreted incorrectly by people who do not understand the cultural values ​​and religious values ​​in the practice of pilgrimage to the tomb of Wali Nyatok.